Developing Speaking Competencies Based on the Audio-Oral (Listening-Speaking) Methodology: A Study on the Example of Students at the International Islamic Academy of Uzbekistan (IIAU) - Mirzaakbarovna, Kadirova Mashkhura (Jurnal Teknologi Pendidikan, 2025)
This study examines the effectiveness of the Audio-Oral (Audiolingual) methodology in developing Arabic speaking competencies among students at the International Islamic Academy of Uzbekistan (IIAU). Employing a qualitative research design, data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis of instructional materials. The findings indicate that the systematic application of listening-based repetition, pronunciation drills, and structured speech modeling significantly improves learners’ phonetic accuracy, auditory discrimination, speech fluency, and confidence in oral communication. The integration of digital tools and gamification strategies further enhances student motivation and supports independent learning beyond the classroom. Despite these positive outcomes, challenges such as limited exposure to a natural Arabic language environment, phonetic interference from learners’ native languages, and instructional monotony remain evident. The study concludes that combining the Audio-Oral method with communicative and digital approaches is essential for optimizing speaking skill development in Arabic language education.